ANALISIS KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK PADA MATERI USAHA DAN ENERGI - Ashshiddiq, Hasbi; Maria S, Haratua Tiur; Hidayatullah, Muhammad Musa Syarif (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
The advancement of knowledge and technology has a significant impact on the development of science education. In the 21st century, technological progress has influenced various aspects of human cognition, including learning processes and critical thinking abilities. Critical thinking skills are essential for personal growth beyond formal education. This study aims to investigate critical thinking skills, such as interpretation, analysis, inference, explanation, and evaluation. Employing a pre-experimental design, the research focuses on 10thgrade science students from the X MIPA 1 class at SMA Negeri 1 Teluk Batang. The sample is selected using a simple random sampling technique. The findings of the study indicate that a majority of the students, approximately 70.37% of the total sample (19 out of 27 students), demonstrate very low or low levels of critical thinking skills across all categories. Moreover, critical thinking skills in areas like analysis, inference, and evaluation also show relatively low levels. Therefore, it is recommended that future researchers utilize appropriate teaching methods to enhance students' critical thinking skills in each category and aspect being observed.